2022
DOI: 10.1038/s41537-022-00301-4
|View full text |Cite
|
Sign up to set email alerts
|

Three-year outcomes and predictors for full recovery in patients with early-stage psychosis

Abstract: In the present study, various outcomes over 3-year period in patients with early stage psychosis including remission, recovery, relapse and medication adherence were investigated. Predictor for full recovery at year 3 was also examined. Three-year follow-up data in 534 patients with schizophrenia spectrum disorders (SSD) and psychotic disorder not otherwise specified (PNOS) were examined for overall outcome trajectories. The data of completers at year 3 (n = 157) were used to identify predictors for recovery u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Some of the previous studies report that longer DUP predict less recovery after 3 months of treatment even after controlling for all the determinants of DUP and severity of symptoms at baseline (Drake et al, 2000). Other studies report longer DUP to be a predictor of poorer long term social functioning and symptomatic as well as functional recovery (Li et al, 2022; Novak Sarotar et al (2008), Qin et al (2014); Sarotar et al, 2008). These findings taken together suggest that to improve personal recovery of patients with FEP, clinicians should lay emphasis on reducing the DUP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the previous studies report that longer DUP predict less recovery after 3 months of treatment even after controlling for all the determinants of DUP and severity of symptoms at baseline (Drake et al, 2000). Other studies report longer DUP to be a predictor of poorer long term social functioning and symptomatic as well as functional recovery (Li et al, 2022; Novak Sarotar et al (2008), Qin et al (2014); Sarotar et al, 2008). These findings taken together suggest that to improve personal recovery of patients with FEP, clinicians should lay emphasis on reducing the DUP.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of basal impairment in cognitive functions and poorer premorbid adaptation also predict poor recovery after 3 years after a FEP (Treen Calvo et al, 2018). Studies have also found duration of untreated psychosis (DUP), family intimacy and physical activity as predictors of recovery in patients with FEP (Li et al, 2022). Family variables like expressed emotions have also been found to predict the FEP (Haidl et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These defences do not require higher-level cognitive and symbolic functioning (Lucus 2009;Gabbard 2014). Around 30-40% of illnesses that present to mental health services with psychotic symptoms recover and full symbolic functioning is regained (Li 2022). It is worth noting that a transient psychotic state can occur when the brain is strained or tired and with some drugs, such as cannabis and alcohol.…”
Section: Primary Psychotic Illnessmentioning
confidence: 99%
“…The life expectancy of patients with SZ is 15–20 years shorter than the life expectancy of the general population [ 1 ], and the age-standardized disability-adjusted life-years is reportedly 12.2% [ 2 ]. However, there is increasing evidence that psychotic patients, particularly individuals experiencing first-episode psychosis, can achieve favorable clinical outcomes, such as symptomatic remission and functional recovery [ 3 , 4 ]. For individuals who achieved both symptomatic and functional recovery, there is a need to determine when and how antipsychotic medication should be discontinued.…”
Section: Introductionmentioning
confidence: 99%
“…They showed altered functional connectivity (FC) [ 11 ], as well as changes in the activities of specific brain regions, while the patients performed tasks [ 10 , 12 ]. However, the participants in those studies did not meet our strict criteria for full recovery [ 3 , 5 ]. SZ has been explained in terms of aberrant interactions among brain regions, leading to the degeneration of brain networks; this degeneration is referred to as disconnection syndrome [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%